Trends in risk factors of anastomotic leakage after colorectal cancer surgery (2011–2019): A Dutch population‐based study. (7th October 2021) - Arron, Melissa N. N.; Greijdanus, Nynke G.; ten Broek, Richard P. G.; Dekker, Jan Willem T.; van Workum, Frans; van Goor, Harry; Tanis, Pieter J.; de Wilt, Johannes H. W.
Abstract: Aim: Anastomotic leakage (AL) after colon cancer (CC) and rectal cancer (RC) surgery often requires reintervention. Prevalence and morbidity may change over time with evolutions in treatment strategies and changes in patient characteristics. This nationwide study aimed to evaluate changes in the incidence, risk factors and mortality from AL during the past nine years. Methods: Data of CC and RC resections with primary anastomosis were extracted from the Dutch Colorectal Audit (2011–2019). AL was registered if requiring reintervention. Three consecutive cohorts were compared using logistic regression analysis. Results: Incidence of AL after CC surgery decreased from 6.6% in 2011–2013 to 4.8% in 2017–2019 and increased from 8.6% to 11.9% after RC surgery. In 2011–2013, male sex, ASA ≥3, (y)pT3‐4, neoadjuvant therapy, emergency surgery and multivisceral resection were identified as risk factors for AL after CC surgery. In 2017–2019, only male sex and ASA ≥3 were risk factors for AL. For RC patients, male sex and neoadjuvant therapy were a risk factor for AL in 2011–2013. In 2017–2019, transanal approach was also a risk factor for AL. Postoperative mortality rate after AL was 12% (CC) and 2% (RC) in 2017–2019, without significant changes over time. Conclusion: Contradictory trends in incidence and mortality for AL were observed among CC and RC surgery with changing risk factors over the past 9 years. High mortality after AL is only observed after CC surgery and remains unchanged. Continued efforts should be made to improve early detection and treatment of AL for these patients.